Study on Wax Deposition Law in Daqing Gulong Shale Oil - Zhao Xuefeng; Wang Yunchen; Zhao Zhongshan; Leng Dongmei; Liu Qin; Li Jionghao (E3S Web of Conferences, 2024)
Daqing Gulong shale oil exhibits elevated wax content, a high wax precipitation point, and a high freezing point. However, its oil density and viscosity are relatively low, making it susceptible to wax crystal precipitation. The risk of pipeline clogging is heightened in lower ambient temperatures, posing a hazard to the safe production of shale oil. This study focuses on testing the fundamental physical properties of crude oil. The wax deposition flow loop was employed to replicate wax deposition in extracted fluids under actual high-flow gas-liquid conditions within a pipeline. The deposition patterns were determined based on the experimental findings. The results indicate that, irrespective of whether in single-phase, gas-liquid two-phase, or oil-gas-water three-phase conditions, the deposition mass rises with decreasing oil temperature. Furthermore, the deposition mass rises with an increased temperature difference between the oil and the pipeline wall. Conversely, the deposition mass declines with an increased gas-liquid ratio, and the deposition thickness declines with elevated water content. The observed deposition patterns highlight the significant influence of molecular diffusion and the impact of gas phase shear. These experimental findings offer valuable references and insights for the transportation of Daqing shale oil through pipelines.